ความหลากหลายทางพันธุกรรมของเห็ดโคน Termitomyces straitus (Beeli) Heim โดยใช้ลำดับเบสไอทีเอส - สายรัก กวางแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
Termite mushroom is classified in genus Termitomyces. The Termite mushroom sample collection from many province were brought to be identified for species Termitomyces striatus (Beeli) Heim. It was found that this species of mushroom could grow in many provinces. From these provinces, 17 samples were collected from 5 provinces, such as Khanchnabuti, Nakornpatom, Uthaithani, Petchaburi and Tak. The tissue of 17 samples were cultured on solid media, PDA and in liquid media, PDB for DNA extraction from mycelium. The extracted DNA from the samples were subjected to sequencing and studied on it ITS region using ITS primers. It was found that DNA sequences of among each 17 samples has 600-700 nucleotides long. Comparison on DNA sequences, revealed the homology value of 99-100%. From DNA alignment and phylogenetic analysis, relationship among termite mushroom in this study can be devided into two groups which hold different characteristic from that of Indonesia one.